The Wnt Target Gene L1 in Colon Cancer Invasion and Metastasis - Haase, Gal; Gavert, Nancy; Brabletz, Thomas; Ben-Ze'Ev, Avri (Cancers, 2016)
The Wnt-?-catenin signaling pathway is highly conserved during evolution and determines normal tissue homeostasis. Hyperactivation of Wnt-?-catenin signaling is a characteristic feature of colorectal cancer (CRC) development. ?-catenin is a major transducer of the Wnt signal from the cytoplasm into the nucleus where it acts as a co-transcriptional activator of ?-catenin-TCF target genes. ?-catenin is also required for linking cadherin type cell-cell adhesion receptors to the cytoskeleton, and consequently Wnt-?-catenin signaling is an attractive system for investigating the role of adhesion-mediated signaling in both normal intestinal tissue homeostasis and CRC development. In this review, we summarize our studies on one Wnt-?-catenin target gene, L1, a member of the immunoglobulin-like cell adhesion transmembrane receptor family. We describe the mechanisms of L1-mediated signaling in CRC cells, its exclusive localization in invasive areas of CRC tissue, and its ability to increase cell motility and confer metastasis to the liver. We discuss the activation (by L1) of genes via an ezrin-NF-?B pathway and the induction of genes also found in the intestinal stem cell signature. By studying L1 (adhesion)-mediated signaling, we expect to learn about mechanisms regulating both normal intestinal homeostasis and CRC development.
EVALuna2:10215